Designing and Validating a Behavioral Model of Banking System Customers - Mir Shafiei, Atyeh Sadat; Taleghani, Mohammad; Saberi Haghayegh, Rahmat Ali (Management Strategies and Engineering Sciences, 2025)
The aim of the present study is to design and validate a behavioral model of banking system customers. The research method is a sequential exploratory mixed-methods approach. In the qualitative section, research participants included university professors in fields related to marketing management and business, as well as heads, deputies, and customer relations managers in Bank Day branches in Tehran, totaling 12 individuals selected through purposive (snowball) sampling based on the principle of theoretical saturation. The data collection tool consisted of semi-structured interviews, and the validity and reliability of the tool were evaluated based on the method proposed by Lincoln and Guba. Data analysis was conducted using thematic analysis (Attride-Stirling method) with MAXQDA 2020 software. In the quantitative section, the research method was descriptive-survey, and the statistical population consisted of Bank Day customers in Tehran. Due to the unlimited population, 410 individuals were selected as the statistical sample using Cochran's formula and stratified random sampling. The data collection tool in this section was a researcher-made questionnaire derived from expert opinions in the qualitative section. To assess the validity of the research tool, construct validity was measured using the Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy and Bartlett's test of sphericity, while reliability was assessed using Cronbach’s alpha coefficient and composite reliability. Quantitative data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics with SPSS 22 and SMART PLS 3 software. The results of the qualitative data analysis led to the identification of four overarching themes (banking services, financial affairs, branch characteristics, and human and communication factors) in the form of ten organizing themes (electronic banking, quality and diversity of banking services, foreign exchange and international operations, banking loans and interest payments, investment, internal and external branch design, branch accessibility and welfare facilities, customers, human resources, marketing and advertising) and 66 basic themes. Ultimately, the findings from the quantitative data analysis indicated that the designed model possesses desirable fit and validity.